Machinability of tool steels machined by electric-discharge machining - Kannachai Kanlayasiri; Prajak Jattakul; Niwat Mookam (SNRU Journal of Science and Technology, 2021)
SKD11 has been a widely used tool steel for cold works for many years while DC53 tool steel is intently developed to replace SKD11. In this paper, the machinability of these two tool steels was compared in terms of material removal rate (MRR), electrode wear ratio (EWR), and arithmetic mean of value of roughness (Ra) of the specimen machined by electric-discharge machining. The machining variables involved were electric-discharge time and electric-discharge peak current. The machining electrode was made from a copper alloy. Results show that both electric-discharge time and electric-discharge peak current had an influential effect on MRR, EWR, and Ra of both tool steels. MRR of SKD11 was significantly higher than that of DC53 while DC53 caused higher EWR than SKD11. It was found that SKD11 provided a better surface finish than DC53. Empirical models for MRR, EWR, and Ra were also presented in this paper.
Keywords: Advanced Machining and Optimization Techniques; Advanced machining processes and optimization; Non-Destructive Testing Techniques